2018
DOI: 10.1080/08923973.2018.1424902
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of trans-cinnamaldehyde on lipopolysaccharide-stimulated macrophage activation via MAPKs pathway regulation

Abstract: TCA elicits the anti-inflammatory effects on LPS-stimulated macrophage activation via suppression of MAPKs phosphorylation, and pro-inflammatory gene expression. Therefore, this study provides important information regarding the use of TCA as a candidate therapeutic agent against inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 30 publications
4
28
0
1
Order By: Relevance
“…Herein, it was found that cinnamaldehyde reduces the production of key inflammatory mediators (IL-17, VEGF and NO) in the wound beds of P. aeruginosa -infected mice. Cinnamaldehyde anti-inflammatory effects are not novel, and different studies have demonstrated its ability to reduce NO and pro-inflammatory cytokine generation upon LPS stimuli [26,35,36,37]. However, its modulatory role on VEGF expression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, it was found that cinnamaldehyde reduces the production of key inflammatory mediators (IL-17, VEGF and NO) in the wound beds of P. aeruginosa -infected mice. Cinnamaldehyde anti-inflammatory effects are not novel, and different studies have demonstrated its ability to reduce NO and pro-inflammatory cytokine generation upon LPS stimuli [26,35,36,37]. However, its modulatory role on VEGF expression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TCA has anti-inflammatory effects [13, 16, 35], such as inhibiting the expression of inflammatory factors like IL-1 ÎČ , NO, and PGE 2 [13, 15, 35]. Nevertheless, whether TCA has benefits against cartilage degradation in OA-like inflammation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, he chose to exam kidney instead of cartilage because he believed it is vulnerable to oxidative stress and inflammation stimuli. Recently, the anti-inflammatory effects of TCA in LPS-induced macrophages produced via the suppression of mitogen-activated protein kinase (MAPKs) phosphorylation and proinflammatory genes were also revealed [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamaldehyde, but not cinnamic acid, cinnamic alcohol and coumarin, inhibits the production of NO, TNFα and PGE2 by LPS-stimulated RAW264.7 cells (1). Cinnamaldehyde was also reported to inhibit the inflammatory activity of LPS-stimulated macrophages via suppression of mitogen-activated protein kinase (MAPK) phosphorylation and pro-inflammatory gene expression (67). Furthermore, it has been reported that when RAW264.7 macrophages were treated with cinnamaldehyde together with E. coli LPS, significant concentration-dependent inhibition of NO, TNFα, and PGE2 production was detected (1).…”
Section: Stimulation Of Ho1 Mrna Expression By Cinnamates and (Meth)amentioning
confidence: 99%